Polarimetric Observations of Hungaria Asteroids - Gil Hutton, Ricardo Alfredo (2007)
Aims. We present the results of a polarimetric program at Complejo Astronómico El Leoncito (Casleo), San Juan, Argentina. The aim of this campaign is to estimate the polarimetric properties of asteroids belonging to the Hungaria dynamical group. Methods. The data were obtained with the Casprof polarimeter at the 2.15 m telescope. The Casprof polarimeter is a two-hole aperture polarimeter with rapid modulation. The campaign began in 2000, and data on a sample of 24 members of the Hungaria group were obtained. We use the slope - albedo or Pmin - albedo relationships to get polarimetric albedos for 18 of these objects. Results. Only two Xe-type objects, 434 Hungaria and 3447 Burkhalter, shown a polarimetric behavior compatible with a high albedo object. The A-type asteroid 1600 Vyssotsky has a polarimetric behavior similar to what was observed by Fornasier et al. (2006) for 863 Benkolea, and four objects show Pmin values consistent with dark surfaces.